2014
DOI: 10.1080/08897077.2014.933726
|View full text |Cite
|
Sign up to set email alerts
|

An International Perspective and Review of Cocaine-Induced Psychosis: A Call to Action

Abstract: Cocaine use can induce transient psychotic symptoms that include suspiciousness, paranoia, hallucinations, and other cocaine-related behaviors. In this commentary, the authors provide an international perspective while reviewing the recent advances in epidemiology, clinical features, and risk factors related to cocaine-induced psychosis exhibited by patients with cocaine use disorders. In some settings, the occurrence of cocaine-induced psychosis has been shown to be as high as 86.5%. Many risk factors have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 58 publications
(184 reference statements)
3
21
0
5
Order By: Relevance
“…Psychotic disorders were more frequent in patients treated concomitantly for cocaine abuse, in agreement with previous studies showing an association between manic episodes and the use of CNS stimulants (Dalmau et al, 1999;Maremmani et al, 2012;Schuckit, 2006) and specifically between psychotic symptoms and the use of cocaine (Roncero et al, 2014a;Roncero et al, 2014b). Additionally, there were more men with psychotic disorders, while women suffered more frequently from sexual and gender identity disorders, consistent with previous studies in OD patients that showed an association between certain psychiatric disorders and gender.…”
Section: Discussionsupporting
confidence: 87%
“…Psychotic disorders were more frequent in patients treated concomitantly for cocaine abuse, in agreement with previous studies showing an association between manic episodes and the use of CNS stimulants (Dalmau et al, 1999;Maremmani et al, 2012;Schuckit, 2006) and specifically between psychotic symptoms and the use of cocaine (Roncero et al, 2014a;Roncero et al, 2014b). Additionally, there were more men with psychotic disorders, while women suffered more frequently from sexual and gender identity disorders, consistent with previous studies in OD patients that showed an association between certain psychiatric disorders and gender.…”
Section: Discussionsupporting
confidence: 87%
“…1,2 Patients with substance use disorders (SUD) and other comorbid mental disorders are called dual diagnosis or dual disorder patients (DD). These patients have little awareness of their disease.…”
Section: Introductionmentioning
confidence: 99%
“…La prise de MA est donc associée, pour plusieurs, à des problèmes de santé mentale graves persistant même après l'arrêt de la consommation. Ces prédicteurs ressemblent beaucoup aux pré-dicteurs de symptômes psychotiques transitoires retrouvés chez les utilisateurs de cocaïne (Roncero et al, 2014). Toutefois, les études portant sur la cocaïne ne semblent pas avoir examiné les prédicteurs de symptômes psychotiques persistants.…”
Section: Profils Des Personnes Utilisatrices De Ma Présentant Des Symunclassified